Efforts to Improve Mathematic Reasoning Abilities and Self Efficacy with E-Learning Methods Based on Google Suite and Geogebra Applications on Circle Subject Grade XI MIPA SMAK PENABUR Kota Jababeka - Lukman El Hakim; Romada Rumahorbo; Lukita Ambarwati (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2020)
The physical distancing policy to prevent the spread of the Covid 19 outbreak, which was established by WHO as a global pandemic on March 12, 2020, affects various aspects of life. Distance learning is an implementation of physical distancing policies in the field of education. The purpose of this study in general is to provide an alternative interactive distance learning method, namely by using e-Learning learning methods assisted by google suite and geogebra to improve mathematical reasoning skills and self-efficacy of class XI MIPA students of SMAK PENABUR Kota Jababeka. The subjects in this study were 6 students, three male students and three female students. The results of this research indicate that use e-Learning method based on Google Suite and Geogebra Applications can improve mathematical reasoning skills and self efficacy. The average score of students' mathematical reasoning ability test of class XI MIPA in the final test of cycle I was 63.93 with the percentage of the number of students who achieved completeness criteria was 28.12%. In the final test of cycle II, the average score increased to 69.54 with the percentage was 40.63%. In the final test of cycle III, the average score of students' mathematical reasoning ability test increased to 74.33 with the percentage of the number of students who achieved completeness criteria was 67.75%. Meanwhile, the students' self-efficacy scores of class XI MIPA before using the e-Learning method assisted by the Google Suite and Geogebra applications, after which it has increased from 3.20 to 3.30.